Big data and reference intervals: rationale, current practices, harmonization and standardization prerequisites and future perspectives of indirect determination of reference intervals using routine data - Martinez-Sanchez Luisa; Marques-Garcia Fernando; Ozarda Yesim; Blanco Albert; Brouwer Nannette; Canalias Francesca; Cobbaert Christa; Thelen Marc; den Elzen Wendy (Advances in Laboratory Medicine, 2020)
Reference intervals are commonly used as a decision-making tool. In this review, we provide an overview on “big data” and reference intervals, describing the rationale, current practices including statistical methods, essential prerequisites concerning data quality, including harmonization and standardization, and future perspectives of the indirect determination of reference intervals using routine laboratory data.